Anti-plaque effect of a synergistic combination of green tea and Salvadora persica L. against primary colonizers of dental plaque - Abdulbaqi, H.R.; Himratul-Aznita, W.H.; Baharuddin, N.A. (Elsevier, 2016)
Objective Green tea (Gt), leafs of Camellia sinensis var. assamica, is widely consumed as healthy beverage since thousands of years in Asian countries. Chewing sticks (miswak) of Salvadora persica L. (Sp) are traditionally used as natural brush to ensure oral health in developing countries. Both Gt and Sp extracts were reported to have anti-bacterial activity against many dental plaque bacteria. However, their combination has never been tested to have anti-bacterial and anti-adherence effect against primary dental plaque colonizers, playing an initial role in the dental plaque development, which was investigated in this study. Methods Two-fold serial micro-dilution method was used to measure minimal inhibitory concentration (MIC) of aqueous extracts of Gt, Sp and their combinations. Adsorption to hexadecane was used to determine the cell surface hydrophobicity (CSH) of bacterial cells. Glass beads were used to mimic the hard tissue surfaces, and were coated with saliva to develop experimental pellicles for the adhesion of the primary colonizing bacteria. Results Gt aqueous extracts exhibited better anti-plaque effect than Sp aqueous extracts. Their combination, equivalent to 1/4 and 1/2 of MIC values of Gt and Sp extracts respectively, showed synergistic anti-plaque properties with fractional inhibitory concentration (FIC) equal to 0.75. This combination was found to significantly reduce CSH (p < 0.05) and lower the adherence ability (p < 0.003) towards experimental pellicles. Conclusion Combination between Gt and Sp aqueous extracts exhibited synergistic anti-plaque activity, and could be used as a useful active agent to produce oral health care products.